2020
DOI: 10.2147/ott.s232769
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA SPRY4-IT1 Reverses Cisplatin Resistance by Downregulating MPZL-1 via Suppressing EMT in NSCLC</p>

Abstract: Long non-coding RNA (lncRNA) SPRY4 intronic transcript 1 (SPRY4-IT1) is reported to play important roles in the occurrence and development of many tumors. However, the possible role of SPRY4-IT1 in cisplatin (DDP) resistance of non-small-cell lung cancer (NSCLC) remains unclear. The aim of this study is to investigate the functions and molecular mechanisms underlying SPRY4-IT1 of cisplatin resistance in NSCLC. Methods: Expression of SPRY4-IT1 was analyzed in A549 and cisplatin-resistant A549/DDP cell lines by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…[11][12][13][14] Increasing evidence has demonstrated the involvement of LncRNA in cisplatin resistance in multiple human cancers. [47][48][49][50][51] In NSCLC, LncRNA SPRY4-IT1 was reported to reverse cisplatin resistance partially through downregulating MPZL-1 via EMT, 52 and LncRNA NORAD was found to increase cisplatin resistance via the miR-129-1-3p/SOX4 axis. 53 A recent study concluded that LncRNA-XIST contributes to cisplatin resistance through down-regulating miRNA-144-3p.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Increasing evidence has demonstrated the involvement of LncRNA in cisplatin resistance in multiple human cancers. [47][48][49][50][51] In NSCLC, LncRNA SPRY4-IT1 was reported to reverse cisplatin resistance partially through downregulating MPZL-1 via EMT, 52 and LncRNA NORAD was found to increase cisplatin resistance via the miR-129-1-3p/SOX4 axis. 53 A recent study concluded that LncRNA-XIST contributes to cisplatin resistance through down-regulating miRNA-144-3p.…”
Section: Discussionmentioning
confidence: 99%
“…A significant body of evidence has indicated that lncRNAs are aberrantly expressed in NSCLC, which results in cancer progression, unlimited growth, and metastasis. [39][40][41] Moreover, lncRNAs have been identified as contributors to NSCLC etiology and development. 42,43 Therefore, investigating the regulatory activities of lncRNAs in NSCLC may lead to the identification of diagnostic markers and therapeutic targets for this fatal disease.…”
Section: Discussionmentioning
confidence: 99%
“…In general, SPRY4-IT seems to act in a pro-tumorigenic sense, being associated to the development and progression of several tumors, among which breast cancer ( 121 , 122 ), osteosarcoma ( 123 , 124 ), and colorectal cancer ( 125 , 126 ). However, there are some cases in which SPRY4-IT4 has been reported to act as a tumor suppressor, in particular in non-small cell lung cancer ( 127 , 128 ).…”
Section: Long Non-coding Rnas Role In Testicular Cancermentioning
confidence: 99%